Development of Science Literacy-Based Student Worksheets for Fifth Grade Students at Madrasah Ibtidaiyah Ma'arif Maron, Garung - Karimah, Karimah; Majid, Abdul; Shiddiq, Ngarifin; Firdaus, Firdaus; Fatkhana, Nafila Nuru (Journal of Education Technology and Inovation, 2025)
This study aimed to examine the feasibility, effectiveness, and practicality of developing a science literacy-based Student Worksheet for fifth-grade students at Madrasah Ibtidaiyah Ma‚arif Maron. The research employed a research and development (R&D) approach focusing on the Human Digestive System classification topic. The feasibility of the developed Student Worksheet was evaluated through expert validation involving a language expert, a material expert, and a media/design expert. The validation results indicated that the Student Worksheet was categorized as highly feasible, with scores of 80% from the language expert, 92.5% from the material expert, and 87.5% from the media/design expert. The effectiveness and practicality of the Student Worksheet were assessed through student and teacher response questionnaires. The results showed that students responses reached 84.62%, while teachers responses reached 86.67%, both categorized as very feasible. These findings suggest that the science literacy-based Student Worksheet is valid, effective, and practical for supporting science learning and enhancing students scientific literacy in elementary education.